O edukacji w perspektywie tragizmu - Futyma, Sławomir; Rudnicki, Zbigniew (Kultura-Społeczeństwo-Edukacja, 2020)
Man experiences their existence constantly experiencing tension that emerges between that which is and that which could be, between the actual, known, and the unknown that barely shines in the horizon. In this uncomfortable experience, one can find potential for development, hidden behind a facade of pretence and camouflage, which, when disclosed and uncovered can be the “fuel” of satisfactory change. As a result, education can be in service of man once again. This process, as a fundamental experience, will assume the acceptance of truth about the human condition and the circumstances of its emergence in the course of life. Education not abandoning man must rediscover and re-evaluate such categories as fate, uncertainty, fragility, unforeseeability.